The birth of the new justice the internationalization of crime and punishment, 1919-1950 - Lewis, Mark 1968- (Oxford University Press, 2014)
'The Birth of the New Justice' is a history of the attempts to instate ad hoc and permanent international criminal courts and new international criminal laws from the end of World War I to the beginning of the Cold War. The purpose of these courts was to repress aggressive war, war crimes, terrorism, and genocide
Includes bibliographical references and index
Keywords: Geschichte 1900-2000; Geschichte 1919-1950; Geschichte; War crimes / History / 20th century; War (International law); Internationale Strafgerichtsbarkeit; Kriegsverbrecherprozess; Hochschulschrift